Histomorphometric study of the spinal growth plates in idiopathic scoliosis and congenital scoliosis - ZHU, FENG; QIU, YONG; YEUNG, HIU YAN; LEE, KWONG MAN; CHENG, JACK CHUN-YIU (Pediatrics international, 2006)
Background: Previous studies have suggested that the relative anterior spinal overgrowth may play an important role in the etiopathogenesis of spinal deformity in adolescent idiopathic scoliosis (AIS). Little is known about the histomorphometry of the anterior and posterior spinal growth plates. Methods: In the present study, the growth plates from the anterior and posterior column of the spine of the AIS (n = 9) and the congenital scoliosis (CS; n = 9) were harvested intraoperatively. The growth plates were harvested from apical area in AIS patients and from normal region in CS patients. The biopsies were prepared with routine histological methods for quantitative histomorphometric analysis. Apoptosis and cell proliferation of the growth plate chondrocytes were examined by triphosphate‐biotin nick end labeling assay and immunohistochemistry of proliferating cell nuclear antigen antibody. Results: The growth plates of AIS and CS were shown to have normal architectures as the normal growth plate. However, it is shown that the proliferative and hypertrophic chondrocytes in the anterior column of AIS patients was more active in terms of the zonal area and height, proliferative chondrocytes, and apoptotic chondrocytes than that of the posterior column (P < 0.05). The difference found in AIS patients was not observed in CS patients. Conclusion: The difference in histomorphometry and cellular activity between the anterior and posterior column in AIS and CS patients indicated that these two groups of patients have different growth kinetics which may affect the curve development.